CheckMate 171: A phase 2 trial of nivolumab in patients with previously treated advanced squamous non-small cell lung cancer, including ECOG PS 2 and elderly populations. (March 2020) - Felip, Enriqueta; Ardizzoni, Andrea; Ciuleanu, Tudor; Cobo, Manuel; Laktionov, Konstantin; Szilasi, Maria; Califano, Raffaele; Carcereny, Enric; Griffiths, Richard; Paz-Ares, Luis; Duchnowska, Renata; Garcia, Miriam Alonso; et al.
Abstract: Background: CheckMate 171 (NCT02409368) is an open-label, multicentre, phase 2 trial of nivolumab in previously treated advanced squamous non-small cell lung cancer (NSCLC), conducted as part of a post-approval commitment to the European Medicines Agency (EMA). We report outcomes from this trial. Methods: Patients with Eastern Cooperative Oncology Group performance status (ECOG PS) 0–2 and disease progression during/after ≥1 systemic treatment (≥1 being platinum-based chemotherapy) for advanced or metastatic disease were treated with nivolumab 3 mg/kg every 2 weeks until progression or unacceptable toxicity. The primary end-point was incidence of grade 3–4 treatment-related select adverse events (AEs). Other end-points included overall survival (OS) and safety. Results: Of 811 patients treated, 103 had ECOG PS 2; 278 were aged ≥70 years and 125 were ≥75 years of age. Minimum follow-up was ~18 months. Safety was similar across populations; the most frequent grade 3–4 treatment-related select AEs in all treated patients were diarrhoea (1%), increased alanine aminotransferase (ALT, 1%), pneumonitis (0.7%), colitis (0.6%) and increased aspartate aminotransferase (AST, 0.5%). Median OS was similar in all treated patients and those aged ≥70 and ≥75: 10.0 months, 10.0 months and 11.2 months, respectively. Median OS was 5.2 months in patients with ECOG PS 2. Conclusion: These results suggest that nivolumab is well tolerated and active in patients with advanced, relapsed squamous NSCLC, including the elderly, with OS outcomes consistent with phase 3 data. In patients with ECOG PS 2, nivolumab had similar tolerability, but outcomes were worse, as expected in this difficult-to-treat, poor prognosis population. Clinical trial registration: NCT02409368. Highlights: This is the largest trial of nivolumab in patients with relapsed squamous NSCLC. Broader eligibility criteria including ECOG PS 2 and elderly (≥70 and ≥ 75 years). Nivolumab was well tolerated and OS outcomes were similar to CheckMate 017. The clinical profile of nivolumab was similar in the elderly and overall population. Nivolumab was well tolerated but had shorter OS in patients with ECOG PS 2 versus 0–1.